A B O blood groups and age at menarche in a selected group of women from Wroctaw city - Kornafel, Danuta (Anthropological Review, 1978)
The study was aimed at revealing eventual relation between ABO blood groups and maturation rate in a group of 2194 women born 1926 through 1955 living in the city of Wrocław. It has been found that women with blood groups A and AB have significantly lower menarcheal age than those with O and B blood types (tab. 1, 3, fig. 1). Comparing median age at menarche computed for groups of women differing by Rh factor (tab. 4 and 5, fig. 2) only one significant difference was found: when studying jointly Rh and ABO systems Rh negative women with A and O blood groups had menarche slightly earlier than all other women. Dividing material only with respect to Rh, significant result was obtained in that Rh negative individuals mature on the average about 4 months earlier than Rh positive ones. Moreover regular data concerning age at menarche are presented revealing that 59% of studied subjects matured at the age 12.5- 14.5 yrs. including 37% maturing between 13.5 and 14.5 (tab. 1). Average age at menarche in the sample was 13.75 yrs. being at the upper limit established by other authors (tab. 6).